Perception on the importance of English among students of Faculty of Education UiTM Shah Alam / Muhammad Anas Zakwan Sabri - Sabri, Muhammad Anas Zakwan (Faculty of Education, 2014)
The study was conducted to study the perception on the significance of English.lt was intended to study the perception on the significance of English among Semester 4, 6 and 8 students of Faculty of Education, Shah Alam. A total of 75 students from Semester 4, 6 and 8 were chosen as participants. A survey research method was used, for various reason, result indicate that the students from Semester 4 has the highest perception of English and its importance in life.